Fluid resuscitation via colon alleviates systemic inflammation in rats with early-stage severe acute pancreatitis - Tongtian Ni (Nature Portfolio, 2021)
Abstract Fluid resuscitation via colon (FRVC) is a complementary therapeutic procedure for early-stage cases of severe acute pancreatitis (SAP). The expression of intestinal dendritic cell-specific intercellular adhesion molecule 3-grabbing nonintegrin (DC-SIGN) regulates systemic inflammation. This study aimed to investigate the effect of FRVC on the expression of DC-SIGN in the colon tissue of SAP rats and its effect on the early response of systemic inflammatory and multiple organ injury. SAP was induced in rats via retrograde injection of sodium taurocholate into the biliopancreatic duct. DC-SIGN expression of appeared in the proximal and distal colon. Histological characteristics and inflammatory cytokines were examined to compare the effect of FRVC and intravenous fluid resuscitation (IVFR). The results showed that DC-SIGN expression in the proximal colon increased in a time-dependent manner in the early-stage of SAP rats. FRVC inhibited DC-SIGN expression in the proximal colon. Both FRVC and IVFR alleviated histological injuries of the pancreas and colon. However, FRVC had an advantage over IVFR in alleviating lung injury and reducing serum TNF-α, IL-6 and LPS. These results suggest that FRVC treatment might help suppress systemic inflammation and prevent subsequent organ failure in early-stage SAP rats likely through inhibiting DC-SIGN expression in the proximal colon.